Generation and phenotyping of a novel knock-in mouse model of desmoplakin dependent arrhythmogenic cardiomyopathy. (14th October 2021) - Di Bona, A; Scalco, A; Bariani, R; Kuperwasser, N; David, P; Celeghin, R; Della Barbera, M; Pilichou, K; Bauce, B; Rizzo, S; Thiene, G; Pende, M; et al.
Abstract: Background: Arrhythmogenic Cardiomyopathy (AC) is a genetic cardiac disorder, mainly caused by mutations in genes encoding desmosomal proteins, and accounts for most stress-related arrhythmic sudden cardiac deaths (SCD) in the young and athletes. The AC myocardium is hallmarked by cardiomyocyte (CM) death and fibro-fatty replacement, which generate a pro-arrhythmogenic substrate. Several pathogenetic factors in AC remain obscure and better understanding of the disease mechanisms is required to develop novel efficacious therapies to prevent SCD, which are sorely missing. The lexical analogy between desmosomes and desmosomal proteins has originally biased AC research towards CMs, the paradigmatic desmosome-bearing cells in heart. However, the myocardium is composed by different cell types, many of which express desmosomal proteins, albeit in the absence of desmosomes, including CMs, sympathetic neurons, vascular cells and fibroblasts. Notably, AC mutations are transmitted at germline, and thus may manifest in all cell types expressing desmosomal proteins. This might explain why the majority of preclinical AC models, using CM specific over-expression or deletion of the disease-causing mutation, failed to fully recapitulate the human disease phenotype. Hypothesis: On these bases, we aimed to generate a knock-in (KI) AC mouse model for comprehensively studying AC pathogenesis. Methods: As Desmoplakin (DSP) mutations occur in a large part of the Italian AC population, we used CRISP/Cas9 to generate a KI mouse strain harboring the Serine-to-Alanine substitution of S311, the murine homolog of human S299 [Bauce et al, 2005]. We successfully obtained DSPS311A/WT KI founders, which were viable and fertile and after backcrossing for >10 generations, used to expand the new mouse strain. Mouse cardiac phenotype was characterized, at different stages (1, 2, 4, 6, 9 mo.) by functional (i.e. ECHO, telemetry-ECG, chronic exercise) and structural (i.e. EM, standard histology, confocal IF, TUNEL assay) analyses. Molecular/biochemical analyses probed the state of the main pathways involved in AC. Results: Our analyses showed that, starting from 4 mo., DSP homozygous KI mice display contractile dysfunction, worsening during aging, and fibrotic myocardial remodelling with focal fatty lesions, accompanied by frequent arrhythmic beats, which become sustained ventricular arrhythmias upon Noradrenaline administration. Hearts showed desmosome alterations, particularly at advanced disease stages, and lateralization of cx43, which corresponded to the phenotype of human AC hearts. Heterozygous mice showed similar alterations, which only took longer to appear. Exercise accelerated disease progression and increased the incidence of SCD (DSPS311A: SCD=63%, n=11; ctrls: SCD=8%, n=12). Conclusion: Our KI mice replicate the clinical and pathological phenotype of DSP-linked biventricular AC and are thus suited for the mechanistic study of the multicellular origin of the disease. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): PRIN Miur 2015